BODY IMAGES OF CLARICE LISPECTOR AND JOAO GILBERTO NOLL - Magri, Milena [UNESP] (Univ Federal Santa Maria, 2018)
This work aims to analyze some images of body present on the work of Clarice Lispector and Joao Gilberto Noll, linked to experiences of suffering and pleasure. We selected some narratives published during the decades of 1970 and 1980 which present relation to the context of oppression promoted by the military regime. Before the suppression of fundamental rights, through the suspension of the habeas corpus and through the menace of the physical integrity, the body figures like a fundamental element of political resistance.
Keywords: Body; Habeas Corpus; Contemporary Brazilian Literature